Back Cover: A Tryptoline Ring‐Distortion Strategy Leads to Complex and Diverse Biologically Active Molecules from the Indole Alkaloid Yohimbine (Chem. Eur. J. 18/2017). Issue 18 (3rd February 2017) - Paciaroni, Nicholas G.; Ratnayake, Ranjala; Matthews, James H.; Norwood, Verrill M.; Arnold, Austin C.; Dang, Long H.; Luesch, Hendrik; Huigens, Robert W.
Abstract : A tryptoline‐based ring distortion strategy enabled rapid access to an array of complex and diverse molecular scaffolds synthesized from the indole alkaloid, yohimbine. During these investigations, 70 complex and diverse small molecules were synthesized and subjected to a panel phenotype screen. These efforts led to the identification of several biologically active hit compounds, including one compound that demonstrates HIF‐dependent antiproliferative activity in HCT116 (colorectal cancer) cells. More information can be found in the Full Paper by R. W. Huigens III et al. onpage 4327 ff.